Predominant Spaces in Las aventuras del Oso mañoso, by Mainor González Calvo - González Hernández, Carlos Andrés (2025)
An interpretation is provided of the significance of the geographical spaces surrounding the characters during their multiple adventures and of how these places permeate their behaviors considerably at a socio-cultural level. How these areas have been resemantized as violent spaces or spaces that are used for illicit purposes is analyzed. Certain places such as the bar, the brothel and other areas located in the city of San José define a proletarian class that questions its environment, and yet enjoys its transgressions in those social spaces.